2007
DOI: 10.1186/1475-2883-6-9
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre evaluations of two new rapid IgG4 tests (WB rapid and panLF rapid) for detection of lymphatic filariasis

Abstract: In the global effort to eliminate lymphatic filariasis (LF), rapid field-applicable tests are useful tools that will allow on-site testing to be performed in remote places and the results to be obtained rapidly. Exclusive reliance on the few existing tests may jeopardize the progress of the LF elimination program, thus the introduction of other rapid tests would be useful to address this issue. Two new rapid immunochromatographic IgG4 cassette tests have been produced, namely WB rapid and panLF rapid, for dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
0
14
0
2
Order By: Relevance
“…For example, the result revealed that at the highest density treatment, longevity was <3 days; these cohorts may not be, epidemiologically, important in disease transmission, as filarial parasites spend about 10 days within the mosquito to reach infective stage. 2,3,69,70 The reverse can be said for cohorts raised at lower density regimen, especially at 1 larva/10 mL. Further studies are advocated to verify the role of density regimens on vector–parasite interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the result revealed that at the highest density treatment, longevity was <3 days; these cohorts may not be, epidemiologically, important in disease transmission, as filarial parasites spend about 10 days within the mosquito to reach infective stage. 2,3,69,70 The reverse can be said for cohorts raised at lower density regimen, especially at 1 larva/10 mL. Further studies are advocated to verify the role of density regimens on vector–parasite interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the World Health Organization (WHO) recommended mosquito-vector control as a supplemental strategy for eliminating the disease. 2,3 However, effective mosquito-vector control must be predicated on an adequate knowledge of the ecophysiology of the vector species. Ecological interaction among immature mosquitoes is of particular importance as they affect egg hatching, 4 competition, and abundance.…”
Section: Introductionmentioning
confidence: 99%
“…The test presented herein complements the immunoassays commercialized by others to detect serological responses to onchocerciasis and lymphatic filariasis [ 28 ]. These include antibody-based lateral flow assays specific for Ov16 (Alere, Waltham, USA [ 29 ]), Wb123 (Alere, [ 29 ]), Bm14 (Brugia Rapid; Reszon, Selangor, Malaysia, [ 30 ]) and Bm14+R1 (PanLF Rapid, Reszon [ 30 ]), and ELISA assays for Wb123 (InBios, Seattle, USA) and Bm14 (Cellabs, Brookvale, Australia [ 27 ]). Antigen-based tests remain much needed and currently exist only for lymphatic filariasis, where they detect circulating filarial antigen (CFA) on a rapid point-of-care platform (BinaxNOW Filariasis [ 31 ] and Filariasis Test Strip (FTS) [ 32 ], both by Alere) or by ELISA (TropBio Og4C3, Cellabs [ 33 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been shown that patent filarial infection is characterized by a modified Th2 response that is associated with increased frequencies of IL-4- and IL-10-producing CD4 T cells (70, 95). Moreover, IgG4 has been used as a marker of filarial infection diagnosis but also as a marker of immunoregulation (96, 97). Although direct evidence for filarial-induced IL-10 to be involved in the induction of IgG4 class switching has not been established, it has been shown that IL-10 can act on human B cells and induce the production of IgG4 (98, 99).…”
Section: Introductionmentioning
confidence: 99%